2012
DOI: 10.3109/0142159x.2012.642826
|View full text |Cite
|
Sign up to set email alerts
|

Reaching the limits of mandated self-reporting: Clinical logbooks do not predict clerkship performance

Abstract: Even within an integrated longitudinal clerkship framework, our findings are consistent with previous studies showing a negligible relationship between logbooks as an educational process measure and how they relate to educational outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 17 publications
1
17
0
2
Order By: Relevance
“…Two studies of logbooks for undergraduate medical students did not demonstrate an association between a higher caseload volume and higher marks. 19,20 Expert feedback and deliberate practice may improve learning more than volume of clinical encounters in isolation. However, quality feedback depends on expert, motivated teachers.…”
Section: Perspectives Of the Medical Educators Jenny Mcdonald And Stementioning
confidence: 99%
“…Two studies of logbooks for undergraduate medical students did not demonstrate an association between a higher caseload volume and higher marks. 19,20 Expert feedback and deliberate practice may improve learning more than volume of clinical encounters in isolation. However, quality feedback depends on expert, motivated teachers.…”
Section: Perspectives Of the Medical Educators Jenny Mcdonald And Stementioning
confidence: 99%
“…A log book may be a useful tool in assessing the highest level of competence as defined by MILLER [29], but in isolation is inadequate to fully prove competence. Although some surgical studies have suggested a correlation between logbook recorded operative caseload involvement and the development of technical skills along with an encouragement to actively pursue learning opportunities, it has been suggested that logbooks do not deliver sufficient reliability or validity to allow for their use in accreditation purposes, and several studies have shown that they do not correlate with educational outcomes [33][34][35][36][37][38].…”
Section: Competencementioning
confidence: 99%
“…(bl.a. Baxter & Shavelson, 1994;Huang, Almeida, & Roberts, 2012;Lyon, 2011;Solano-Flores, 1999 9(2), 2013…”
Section: Skriftlig Evalueringmentioning
confidence: 99%